The Effect of Graft Type on Vertical Jump Performance After Anterior Cruciate Ligament Reconstruction: A Systematic Review - Krzysztof Kasicki; Grzegorz Błażejewski; Łukasz Rydzik; Piotr Wróbel; Monika Nowak; Tadeusz Ambroży (Journal of Clinical Medicine, 2026)
Background: Anterior cruciate ligament reconstruction (ACLR) is the standard of care for ACL injuries, and graft choice may influence the recovery of function assessed with vertical jump tests. Objective: To evaluate the effect of graft type on vertical jump performance in adults after ACLR and to synthesise the differences between grafts. Material and Methods: This systematic review was conducted in accordance with the PRISMA 2020 and SWiM guidelines. The following databases were searched: Scopus, Web of Science, PubMed, MEDLINE and SPORTDiscus (EBSCOhost), up to 31 January 2026. Studies with an unambiguously defined graft type and objective jump tests (CMJ, SL CMJ/SL VJ, DVJ/DJ, SJ) were included. Risk of bias was assessed using the RoB 2, ROBINS-I, JBI and MINORS tools, and the certainty of evidence using the GRADE approach. Because of substantial clinical and methodological heterogeneity, a structured narrative synthesis was performed in accordance with the SWiM guidelines; no pooled analysis was undertaken. Results: Forty-seven studies (>3400 participants) were included. BPTB was associated with greater eccentric-phase asymmetry in the bilateral CMJ in the early/intermediate phase compared with HT, with equalisation after 9–12 months. QT provided jump height comparable to HT but a more favourable dynamic valgus profile. Autograft and allograft did not differ in jump performance. Deficits followed a biphasic course: normalisation of symmetry after approximately 2 years, with reduced height/power for up to 5 years. Conclusions: Forty-two of the studies (89.4%) were non-randomised, and the certainty of evidence was low for one clinical question and very low for all others. Studies comparing BPTB with HT showed an association suggesting greater eccentric-phase asymmetry in the bilateral CMJ in the early and intermediate phase after BPTB, but findings were inconsistent and two studies reported no difference. Evidence suggesting that these differences equalise after 9–12 months derives from between-study comparisons. Jump height did not differ between QT and HT; a single study of 26 patients reported smaller dynamic valgus after QT. Autograft and allograft did not differ in vertical jump performance. Registration: This review was registered in the PROSPERO database and is available under the number CRD420261386307.